PENGEMBANGAN VALIDASI METODE DAN PENETAPAN KADAR AKRILAMIDA PADA UBI JALAR GORENG SECARA KROMATOGRAFI LAPIS TIPIS-DENSITOMETRI - Ayik Rosita P (Prodi Farmasi Fakultas Kedokteran Universitas Hang Tuah, 2021)
A thin-layer chromatography (TLC) Densitometric method for analyzing acrylamide in fried sweet potatoes is not reported before. The research aims to determine the development of acrylamide validation and acrylamide concentration in fried sweet potatoes. The retardation factor for evaluating acrylamide uses silica gel column 254 with range 0.4-0.5 and eluate by methanol: benzene (2:1) was analyzed in a maximum wavelength of 200 nm. Linear response of acrylamide standard was tested within a 120-300 ppm concentration range, and the correlation coefficient (r) more remarkable than 0,99, detection limit 17.45 ppm and quantitative limit 52.36 ppm. Sample preparation was performed by ethanol 70%. The precision resulted from 2,67%, and this result was less than 16% (literature). Percentage of recoveries 98,18 %, and in the literature, 98%-102%. The TLC densitometric method is selective, precise, and accurate. Finally, the research showed that fried sweet potatoes contain acrylamide less than 230,32 ng samples, so the selection is very safe to consume.